Retrospective Study: Trends in Patient Safety Incidents in a Private Hospital in Pekalongan Regency - Muaziz, Harits; Irnawati, I (Prosiding University Research Colloquium, 2022)
Patient safety is an important issue in the health sector because it is one of the basic human needs. Trends in Patient Safety Incidents can be used to predict the tendency of a hospital's IKP. This study aims to describe the trend of patient safety incidents in the Pekalongan Regency Private Hospital. The design of this study used trend analysis with a retrospective longitudinal design. The research sample was patient safety incidents at the Pekalongan Regency Private Hospital in the 2009-2020 period as many as 389 cases. The sampling technique used was total sampling. The research instrument used a recapitulation sheet. Data analysis using Univariate data analysis. The results showed that the trend of patient safety incidents in one of the Pekalongan Regency Private Hospitals for the 2009-2020 period experienced an increase from 2009-2013 but then decreased in 2014. The trend of patient safety incidents has fluctuated movements since Year 2014-2020. The average patient safety incident in a private hospital in Pekalongan Regency for the 2009-2020 period was the highest in 2019 at 4.083 and the lowest in 2009 at 0.5. The highest near-injury (NCC) incidence was 179 cases (46%) and the most common type of NNC was the wrong drug/dose/prescription/route as many as 66 cases (36.87%). Recommendations for hospitals need to provide direction to the Patient Safety Team to carry out Root Case Analysis and follow-up to prevent unwanted incidents, patient safety incidents in the future.